Implementation of team-based learning (TBL) in a second year medical school course: does prior experience with TBL improve the impact of this pedagogy? - Carrasco, Gonzalo A.; Gentile, Matthew; Salvatore, Michelle L.; Lopez, Osvaldo J.; Behling, Kathryn C. (BMC medical education, 2022)
Background We have shown that use of Team-based learning (TBL) in a first-year Infectious Diseases (ID) course improved final examination and course performance. Therefore, we implemented TBL in the second-year Women’s Health (WH) course to improve acquisition of course content. We hypothesized that prior experience with TBL in the first-year of medical school would lead to a strong correlation between TBL performance in the first and second years. Methods Our study is a retrospective review of student TBL and final examination performance in the ID and WH courses. The ID course has weekly TBL exercises that cover all course material, while the WH course has one TBL that covers a small portion of the course material. Final examination and TBL individual readiness assurance test (iRAT) scores in the ID and WH courses from three classes ( n = 226) were obtained with institutional review board approval. Statistical analyses were performed including comparisons of means and correlation studies. Results Average WH iRAT scores were significantly higher than ID iRAT scores (9.19 vs. 7.40, p < 0.01), and iRAT scores in both courses were highly correlated ( r = 0.35, p < 0.01). When stratifying students based on WH course performance, in struggling students, iRAT but not final examination scores were higher in the WH course than the ID course (8.73 vs. 7.00, p < 0.01 and 82.45 vs. 80.51, p > 0.05, respectively). Conclusions Our results suggest that prior experience with TBL improves TBL iRAT scores, especially in struggling students. Prior TBL experience is also associated with consistent iRAT performance between first- and second-year courses in high performing students.